THE DEVELOPMENT OF SUPERVISION MODEL OF COMPETENCY BASED TEACHER TO MATHEMATICS TEACHER - -, Meilani (The Journal of Educational Development, 2013)
The main problem of this research is how the competency-based supervision model of effective teachers to improve the competence of teachers of mathematics. The purpose of this research to 1) identify the profile of supervision conducted for math teachers, 2) developing a competency-based supervision model of effective teachers to improve the competence of teachers of Mathematics. This research uses research and development (research and development). Referring to the overall measures developed Borg and Gall, in this study the steps are simplified into three stages: 1) phase of the study, 2) the development stage, and 3) model validation stage. Data collection techniques used in this study were 1) in-depth interviews (in depth interviews), 2) participant observation (participant - observation), and 3) documentation (documentation). Instrument used is human and to analyze the data using analytical techniques descriptive. The results are completion of a competency-based model of supervision of teachers for effective math teachers to improve the competence of teachers of mathematics.